Strategic Design Helps Build a Global Brand in Turkey - Topaloğlu, Fulden; Er, Özlem (Wiley, 2010)
As Turkish brands seek to find a place on the global market, some are discovering design as a powerful tool for competitive advantage. This case study tells the story of VitrA Bath, which is claiming a hard‐won niche on the world market by positioning itself as a design‐led company.